Monte Carlo and Quasi-Monte Carlo methods 2004 - Niederreiter, Harald, (Springer Berlin Heidelberg, 2006)
Invariance Principles with Logarithmic Averaging for Ergodic Simulations -- Technical Analysis Techniques versus Mathematical Models: Boundaries of Their Validity Domains -- Weak Approximation of Stopped Dffusions -- Approximation of Stochastic Programming Problems -- The Asymptotic Distribution of Quadratic Discrepancies -- Weighted Star Discrepancy of Digital Nets in Prime Bases -- Explaining Effective Low-Dimensionality -- Selection Criteria for (Random) Generation of Digital (0,s)-Sequences -- Imaging of a Dissipative Layer in a Random Medium Using a Time Reversal Method -- A Stochastic Numerical Method for Diffusion Equations and Applications to Spatially Inhomogeneous Coagulation Processes -- Non-Uniform Low-Discrepancy Sequence Generation and Integration of Singular Integrands -- Construction of Good Rank-1 Lattice Rules Based on the Weighted Star Discrepancy -- Probabilistic Approximation via Spatial Derivation of Some Nonlinear Parabolic Evolution Equations -- Myths of Computer Graphics -- Illumination in the Presence of Weak Singularities -- Irradiance Filtering for Monte Carlo Ray Tracing -- On the Star Discrepancy of Digital Nets and Sequences in Three Dimensions -- Lattice Rules for Multivariate Approximation in the Worst Case Setting -- Randomized Quasi-Monte Carlo Simulation of Markov Chains with an Ordered State Space -- Experimental Designs Using Digital Nets with Small Numbers of Points -- Concentration Inequalities for Euler Schemes -- Fast Component-by-Component Construction, a Reprise for Different Kernels -- A Reversible Jump MCMC Sampler for Object Detection in Image Processing -- Quasi-Monte Carlo for Integrands with Point Singularities at Unknown Locations -- Infinite-Dimensional Highly-Uniform Point Sets Defined via Linear Recurrences in